Genotypic and Phenotypic Heterogeneity among Mycobacterium tuberculosis Isolates from Pulmonary Tuberculosis Patients - Shamputa, Isdore Chola (American Society for Microbiology, 2004)
Although the heterogeneity of Mycobacterium tuberculosis populations and the existence of mixed infections are now generally accepted, systematic studies on their relative importance are rare. In the present study, 10 individual colonies of each M. tuberculosis isolate (primary isolate) from 97 tuberculosis patients in a primarily human immunodeficiency virus-negative population were screened for heterogeneity and detectable mixed infections by spoligotyping, IS6110-based restriction fragment length polymorphism analysis, and mycobacterial interspersed repetitive unit-variable number of tandem repeat typing. The MICs of antituberculosis drugs for colonies with divergent fingerprints were determined. Infections with different bacterial subpopulations were detected in the samples from eight patients (8.2%), and the frequency of detectable mixed infections in the study population was estimated to be 2.1%. Genotypic variations were found to be independent of the drug susceptibilities, and the various molecular markers evolved independently in most cases. The predominant strains and the primary isolates always had concordant drug susceptibility and MIC testing results. These findings have implications on the interpretation of molecular epidemiology results for patient follow-up and in transmission studies.